The Emotional Journey: An Exploration of Women's Pre-Birth Anxieties - Suryani, Lilis; Kamil, Hajjul; Hasanuddin, Hasanuddin; Yahya, Mustanir; Sulastri, Sulastri (Heca Journal of Applied Sciences, 2024)
Pregnancy is an important period in a woman's life, but it is often accompanied by worries and fears that cause birth anxiety. Anxiety generally varies in intensity from mild to severe. Anxiety has a negative impact on the health of the mother and fetus, and it causes many women to refuse to give birth naturally. This study aims to explore the psychological and emotional dimensions of pregnant mothers' levels of anxiety toward childbirth, identifying the various concerns and factors that cause anxiety. The research design was non-experimental exploratory descriptive, conducted from May to June 2022. Respondents consist of multigravida women with a gestational age of 36–40 weeks (third trimester). The sample was chosen using purposive sampling. The data collection process uses a questionnaire in the form of semi-structured questions. The level of anxiety for multigravida women is moderate anxiety (36.0%), severe anxiety (32.0%), mild anxiety (24.0%), and 4.0% each with severe anxiety and not anxiety. The aspects found are generally feared to have a cesarean delivery (28.0%) and worry about the baby's condition (20.0%). Factors that cause anxiety are generally the condition of the baby (24.0%), illness suffered by the mother (12.0%), and negative experiences about childbirth (12.0%). Multigravida women generally experience various anxieties during labor, which are caused by various factors that influence them. There are aspects of anxiety that are different from previous studies. Screening for anxiety symptoms and education during the antenatal period are necessary.